PENGARUH KOMITMEN ORGANISASIONAL , KEPUASAN KERJA, DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Erina Rulianti; Rita Hannawati pardede (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This research is to analyze the influence of organizational commitment, job satisfaction, organizational culture to organization citizenship behavior. This research was conducted on 72 respondents by using descriptive approach quantitative. Therefore, the data analysis used is statistical analysis in the form of multiple linear regression. The results of this study show partially and simultaneously organizational commitment variable, job satisfaction and organizational culture have an effect on organizational citizenship behavior. This is evidenced from the results of simultaneous tests (F test) and partial test results (t test) also shows significant values ​​of three independent variables that support the hypothesis. Therefore the test result of this research states that there is influence simultaneously between organizational commitment variable, job satisfaction and organizational culture to organizational citizenship behavior